Dukungan Emosional Keluarga dan Teman Sebaya terhadap Self-Compassion pada Mahasiswa saat Pandemi COVID-19 - Pratista Arya Satwika; Rini Setyowati; Fika Anggawati (Jurnal Psikologi Teori dan Terapan, 2021)
The purpose of this study was to determine the relationship between family and peer emotional support and self-compassion among the final year undergraduate students amid COVID-19 pandemic. A total number of 61 undergraduate students whose ages ranged from 19 to 26 years and who are completing their thesis at the time of this study were selected randomly. Data were collected using questionnaires of self-compassion, and family and peer emotional support which were distributed online. The results of multiple linear regression analysis show that there is a significant relationship between emotional support from family and peers with self-compassion. However, when the analysis was conducted partially, only the relationship between family emotional support and self-compassion that is significant; while, the relationship between peer emotional support and self-compassion is not proved. It can be concluded from the results that there is a simultaneous relationship between family emotional support and peer emotional support with self-compassion owned by students who are completing their thesis during the COVID-19 pandemic.Keywords: Emotional support, family, peer, self-compassion, students Abstrak: Penelitian ini bertujuan untuk menguji hubungan antara dukungan emosional keluarga dan teman sebaya dengan self-compassion pada mahasiswa tingkat akhir pada masa pandemic COVID-19. Sejumlah 61 mahasiswa yang sedang menyelesaikan tugas akhir dengan rentang usia 19 sampai 26 tahun direkrut menggunakan teknik random sampling. Data dikumpulkan menggunakan skala self-compassion, dan dukungan emosional keluarga dan teman sebaya. Berdasarkan hasil analisis regresi linier berganda, diketahui bahwa terdapat hubungan yang signifikan antara dukungan emosional keluarga dan teman sebaya dengan self-compassion. Secara parsial, terdapat hubungan yang signifikan antara dukungan emosional keluarga dengan self-compassion, namun tidak terdapat hubungan antara dukungan emosional teman sebaya dengan self-compassion.  Dapat disimpulkan bahwa terdapat hubungan secara simultan antara dukungan emosional keluarga dan dukungan emosional teman sebaya dengan self-compassion yang dimiliki oleh mahasiswa yang sedang menyelesaikan skripsi pada masa pandemi COVID-19.